(untitled) (Journal of Nepal Geological Society, 2016)
The rainwater penetrating the soil and reaching the zone of weakness develops lifting force, which leads overlying soil mass to slide. Hence, it is important to identify where groundwater exists or flows in the soil, as it indicates where to place countermeasure works. The ground temperature measurement is suitable for assessing groundwater condition, and is easily performed with simple instrument and tool. The result of analysing temperature distribution at the surveying site can provide information on groundwater flowing area. In this paper, we introduce the theory and practice of the ground temperature measurement first, then present a case study of successful landslide survey and mitigation work in Japan, and recommend to apply the similar initiative to the potential landslide area in Bhutan.